Exponential stabilization and L2‐gain for uncertain switched nonlinear systems with interval time‐varying delay. (11th January 2016) - Dong, Yali; Li, Tianrui; Mei, Shengwei
Abstract : This paper is concerned with the exponential stabilization and L 2 ‐gain for a class of uncertain switched nonlinear systems with interval time‐varying delay. Based on Lyapunov–Krasovskii functional method, novel delay‐dependent sufficient conditions of exponential stabilization for a class of uncertain switched nonlinear delay systems are developed under an average dwell time scheme. Then, novel criteria to ensure the exponential stabilization with weighted L 2 ‐gain performance for a class of uncertain switched nonlinear delay systems are established. Furthermore, an effective method is proposed for the designing of a stabilizing feedback controller with L 2 ‐gain performance. Finally, some numerical examples are given to illustrate the effectiveness of the theoretical results. Copyright © 2016 John Wiley & Sons, Ltd.